Responsible Citizens against an Irresponsible State: The Case of Greece amidst the COVID-19 Pandemic - Alexopoulou, Sofia; Pavli, Antonia (HAPSc Policy Briefs Series, 2021)
How is it possible for citizens to act responsibly if they live in an irresponsible state? This is the key question that this paper revolves around in the context of the COVID-19 pandemic in Greece. Individual responsibility is the dominant ‘mantra’ of post-modernity and is widely spread by the neoliberal dogma. The individual has to take care of him/herself in any possible way to avoid risks without depending so much on the benevolent state, which, in the developed world, takes the form of a welfare state. Thus, a new type of citizen appears, the “responsible citizen”. The oxymoron, however, in the Greek case is that the state and particularly the political elites maintain bad practices of the past without being able to overcome the country’s path-dependency structures by acting responsibly. The concept of “empathy” is undoubtedly the missing link in this intriguing puzzle of good governance. Will the Greek political elites be able to recognize and embrace empathy in practice?